Replication in economics - Daniel S. Hamermesh (Institute for the Study of Labor (IZA), 2007)
This examination of the role and potential for replication in economics points out the paucity of both pure replication checking on others' published papers using their data and scientific replication using data representing different populations in one's own work or in a Comment. Several controversies in empirical economics illustrate how and how not to behave when replicating others' work. The incentives for replication facing editors, authors and potential replicators are examined. Recognising these incentives, I advance proposals aimed at journal editors that will increase the supply of replication studies, and I propose a way of generating more scientific replication that will make empirical economic research more credible.
urn:nbn:de:101:1-20080402141
Keywords: 330; Urheberrecht; Publikationsanalyse; Wirtschaftswissenschaft